Modeling financial statements for small and medium businesses in Worm-Made Fertilizer Using Finite State Automata (FSA). Issue 1 (June 2021) - Yuniar Rahman, Aviv; Wanditya Setiawan, Feddy; Lia Hananto, April; Setyawan, Bagus
Abstract: Malang Raya is currently a city that has very rapid economic development. In its development, it began with several small businesses. It is various businesses in Malang such as the culinary, home industry, to livestock business. Currently, one example of a rapidly increasing business is small and medium-sized businesses. Small and medium businesses aim to attract the attention of customers in buying. In this business, there must be financial reports as support in processing business financial data. With this, a State Automata (FSA) finite is needed. Finite State Automata is a concept model that shows the design of an application. With the concept of Finite State Automata, it will introduce a pattern that is in the cash application system. In this test, it will make 3 designs to do the test results. In the three test results it is known that for the first test, it is explained that in the processing process that is carried out 5 times, there is an error in processing 3 times, and in the second test process that is done 5 times, there is an error in processing as much as 1 time. In the third test, this is the result of developing the first and second designs. From the results, it is known that in processing data 5 times, there are no errors in calculations. To test the speed in processing data is appropriate and significant enough to be used as a cash management application for a business.